Reconstructing Judicial Authority in the Annulment of Arbitral Awards: Between Finality and Substantive Justice - Khairunnisa Siregar; Suci Hidayati Malau; Raja Muda Pahlevi Siregar; Ahmad Yasin Dongoran; Arifuddin Muda Harahap (Jurnal Cendikia ISNU SU, 2026)
This study examines the annulment of arbitral awards within the Indonesian legal system as an extraordinary legal remedy that lies at the intersection of arbitral autonomy, the principle of finality, and the pursuit of substantive justice. The research is motivated by the persistent tension between the final and binding character of arbitral awards and the necessity of judicial intervention to address awards affected by fundamental procedural defects. Employing normative legal research, this study adopts statutory, conceptual, and comparative approaches. Legal materials are collected through library research and analyzed using descriptive, systematic, and prescriptive legal reasoning. The findings reveal that Law Number 30 of 1999 on Arbitration and Alternative Dispute Resolution confines annulment to three narrowly defined procedural grounds document forgery, newly discovered decisive evidence, and fraud thereby excluding judicial review of the substantive merits of arbitral awards. Nevertheless, judicial practice demonstrates inconsistent interpretations that occasionally expand the scope of annulment beyond its statutory limits, resulting in judicial overreach and weakening the final and binding nature of arbitration. This study argues that the legitimacy of annulment should be understood as a procedural safeguard rather than a mechanism for substantive review and proposes a Balanced Annulment Doctrine, under which judicial intervention is justified only to preserve procedural integrity while respecting arbitral autonomy. The study concludes that maintaining a proportionate balance between legal certainty, minimum judicial intervention, and substantive justice is essential to strengthening the credibility of arbitration and enhancing Indonesia's legal certainty in commercial dispute resolution.